Penerapan Teori Antrian untuk Meningkatkan Efisiensi Waktu bagi Pasien Rawat Jalan BPJS di Rumah Sakit Royal Surabaya - Betsy Tiurma Pasaribu; Ulfi Pristiana; Estik Hari Prastiwi (Journal of Economics, Management, and Accounting, 2025)
This study evaluates the performance of the BPJS outpatient registration queue at Royal Hospital Surabaya. Observations show a patient arrival rate (λ) of 270 patients per hour, while the service rate per counter (μ) is only 10.676 patients per hour with two active servers. This imbalance results in a server utilization rate (ρ) of 12.64, leading to an average waiting time of approximately 75 minutes and an average queue length of about 25 patients, both exceeding the hospital’s service standards. Simulation results indicate that increasing the service rate to 20 patients per hour is the most effective intervention for reducing waiting time and improving system stability. The combination of a higher μ with a reduced arrival rate through online registration further shortens queues and creates a more balanced flow of patients. The study concludes that the primary cause of congestion is the structural mismatch between patient arrival intensity and service capacity. These findings provide a data-driven basis for operational strategies aimed at enhancing the efficiency and service quality of BPJS outpatient registration.